INTEGRASI ILMU, AGAMA DAN FILSAFAT DALAM ILMU KOMUNIKASI - Nur Ainiyah; Mokhammad Baharun; Erfan Zainul Fanan (Fakultas Dakwah Universitas Ibrahimy, 2023)
The integration of science, religion, philosophy and communication is a consequence of the development of science, where knowledge develops not only with the science itself, but requires other knowledge, especially axiologically in the utilization of science for mankind. The science of communication is the science of conveying information from the communicator to the communicant so as to create the same meaning between the two. Axiologically, it has the same goal as philosophy and religion, namely scientific (scientific) truth. So in this article scientific integration discusses; ontological integration, integration of scientific classification, integration of religious and rational (secular) sciences and finally methodological integration. So that in the end they found a new scientific formulation, namely the philosophy of communication science.